2015
DOI: 10.1007/s12649-015-9384-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Removal of Oil Droplets from Oil-in-Water Emulsions Using Polyethylenimine-Modified Rice Husk

Abstract: Although several nano-materials have been used to adsorb oil droplets in water, preparing these materials requires complex procedures and expensive reagents. Their implication to the environment also remains unclear. Thus, in this study, we propose to develop efficient, inexpensive and environmental-friendly oil-removing adsorbents. To this end, we select an agricultural waste, rice husk (RH), as an adsorbent. To enhance the oilremoving performance, RH are modified with a biocompatible cationic polymer, polyet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The pseudo-second-order rate implies that the rate of adsorption decreased with time. In a similar work (Lin and Chen 2015) on polyethyleneimine modified rice husk, the pseudo-second-order kinetic equation provided the best fit with R 2 > 0.998.…”
Section: Adsorption Kineticsmentioning
confidence: 77%
“…The pseudo-second-order rate implies that the rate of adsorption decreased with time. In a similar work (Lin and Chen 2015) on polyethyleneimine modified rice husk, the pseudo-second-order kinetic equation provided the best fit with R 2 > 0.998.…”
Section: Adsorption Kineticsmentioning
confidence: 77%
“…158 Moreover, research showed that some materials after chemical activation exhibit good oil adsorption capability for the separation of oil-in-water emulsions. 159,160 The superwetting absorbent materials used to separate oil-in-water emulsions are listed in Table 7.…”
Section: Adsorption Typementioning
confidence: 99%
“…Mineral and waste types adsorbents such as carbon nanotubes [12][13][14], clay/anthracite composite [15], wool fibers [16], bentonite [17], carbonized rice husk [18,19] and aminefunctional agricultural wastes [20] have been used to remove oil droplets from oily wastewater.…”
Section: Introductionmentioning
confidence: 99%